The Impact of Incorporating Varied Sand Powder on the Compressive Strength of Concrete (Including Air Addition) - Sutandar, Erwin; Budi, Gatot Setya; Aryanto, Aryanto; Parabi, Ashraf Dhowian (Jurnal Teknik Sipil, 2025)
Concrete is a primary construction material composed of a mixture of aggregates, cement, and water, where the proportion of each component significantly influences its physical and mechanical properties. A common issue in conventional concrete production is a reduction in strength due to uncontrolled porosity and poor air distribution. This study aims to evaluate the effect of sand powder substitution on concrete characteristics and to determine the optimal composition that enhances mechanical performance without compromising material efficiency. The experimental tests were conducted at the Materials and Construction Laboratory, Faculty of Civil Engineering, Universitas Tanjungpura, using a sand powder variation of 0%, 5%, and 10%. The tested parameters included unit weight, compressive strength, splitting tensile strength, flexural strength, and elastic modulus at curing ages of 3 to 28 days. The results showed that conventional concrete achieved the highest compressive strength of 34.802 MPa at 28 days, while the mixtures with 5% and 10% sand powder reached 26.26 MPa and 25.917 MPa, respectively. Although the substitution of sand powder reduced mechanical strength, its use has the potential to enhance construction sustainability by reducing the consumption of natural sand and utilising mineral waste as a replacement material.